1s-like, 2p−-like and 2p+-like States of a Hydrogenoid Impurity in a Cylindrical Quantum Dot Under the Action of an Applied Magnetic Field (2023)
The quantum states of a cylindrical quantum dot (CDQ) of GaAs/Ga0.6Al0.4As are studied theoretically with a hydrogen-like impurity inside and under the action of a uniform magnetic field, applied in the axial direction of the cylinder. Using the variational method, the energies and wave functions of the impurity states, 1s-like, 2p−-like and 2p+-like, when she moves inside the CQD. It was found that there is degeneracy in the impurity energy for the 2p−-like and 2p+-like states in the absence of a magnetic field. This degeneracy is broken only by applying a magnetic field, indicating a Zeeman effect in the system, thus, the variation of the intensity of the magnetic field allows to tune the resonance condition of two photons.